Cyberbullying : Pola Perilaku, Faktor Pemicu, dan Dampak Psikologis - Puja Setia Kirana; Marsha Jihan Alisah; Marta Erika Putri; Risma Anita Puriani; Rizki Novirson (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Cyberbullying is an increasingly worrying social problem in the digital era, especially among adolescents and students. This study aims to examine the behavior patterns, trigger factors, and psychological impact of cyberbullying behavior. The method used was literature review. The samples used were journals published on googlescholar, researchgate and garuda (national reference garba). Article findings are limited from 2020-2025. The results of the research reviewed show that cyberbullying is mostly influenced by social conformity, where a person tends to follow along without thinking. In addition, external factors such as the rapid development of technology and weak social control also exacerbate this phenomenon. The impact can be very serious, ranging from decreased self-confidence, excessive anxiety, to psychological disorders such as depression and a tendency to isolate oneself. Furthermore, an understanding of the behavior patterns, triggering factors, and psychological impact can be the basis for designing more effective interventions to prevent and address cyberbullying in the future.